Dragon Fruit Peel Waste (Hylocereus undatus) as a Potential Ingredient for Reducing Lipid Peroxidation, Dietary Advanced Glycation End Products, and Starch Digestibility in Cookies - Siriwan Chumroenvidhayakul; Thavaree Thilavech; Mahinda Abeywardena; Sirichai Adisakwattana (MDPI AG, 2023)
Excessive consumption of cookies has been linked to harmful health outcomes owing to the presence of refined carbohydrates and heat-induced toxicants including end products of lipid peroxidation and dietary advanced glycation end products (dAGEs). To address this issue, this study explores the addition of dragon fruit peel powder (DFP), which is rich in phytochemicals and dietary fibers, to cookies as a potential solution to mitigate their adverse effects. The results indicate that adding DFP at 1%, 2%, and 5% w/w of raw cookie dough significantly improves the total phenolic and betacyanin contents and antioxidant activity, as evidenced by increased ferric-reducing antioxidant power. DFP incorporation also led to reductions in malondialdehyde and dAGEs (p < 0.05). Furthermore, the starch digestibility, hydrolysis index, and predicted glycemic index were all reduced in the presence of DFP, with the latter estimate being due to the higher content of undigested starch. Incorporating DFP in cookies resulted in significant changes in their physical properties, including texture and color. However, sensory evaluation indicates that the overall acceptability of the cookies was not negatively impacted by the addition of up to 2% DFP, suggesting that it is a viable option for enhancing the nutritional value of cookies without compromising their palatability. These findings suggest that DFP is a sustainable and healthier ingredient that can improve the antioxidant capacity of cookies while also mitigating the harmful effects of heat-induced toxins.